14 A Systematic Review of the Prevalence and Implications of Frailty in Diabetes Mellitus. (16th March 2021) - Hanlon, P; Faure, I; Corcoran, N; Butterly, E; Lewsey, J; McAllister, D A; Mair, F S
Abstract: Background: Frailty, an age-related state of vulnerability to adverse health outcomes, is an important factor in the management of diabetes. This systematic review aims to summarise the observational data on prevalence of frailty in diabetes and the association between frailty and generic (e.g. mortality) and diabetes specific (e.g. hypoglycaemia) outcomes. Methods: We searched three electronic databases for observational studies assessing frailty in adults (≥18 years) with diabetes (type 1, type 2, or unspecified). Eligible studies quantified the prevalence or incidence of frailty or the association between frailty and clinical outcomes in the context of diabetes. Results: 118 studies included, using 18 different frailty measures. Frailty phenotype was the most used (n = 69) followed by frailty index (n = 16) and the FRAIL scale (n = 10). Studies were highly heterogenous in terms of setting (88 community, 18 outpatient, 10 inpatient, 2 residential care), population demographics, and inclusion criteria. The median frailty prevalence in community-based studies using the frailty phenotype was 13% (interquartile range 7-18%). Frailty was identified in "middle-aged" (<65 years) as well as older people with diabetes. Diabetes was consistently associated with incident frailty. Frailty was associated with higher mortality, hospital admission, incident disability. Frailty was associated with hypoglycemic events in 1/1 study. Frailty was also associated cross-sectionally with micro- and macro-vascular complications, lower quality of life, and cognitive impairment. Frailty was not associated with difference in mean HbA1c, however people with frailty were more likely to have high (>9%) or low (<6.5%) HbA1c. Conclusions: Frailty in diabetes is common but inconsistently measured. Frailty is associated with a range of adverse outcomes. Research gaps include the relationship between frailty and glycaemia (particularly hypoglycaemia and the relationship between HbA1c and outcomes in the context of frailty), and the impact of frailty in specific groups such as middle-aged people and in low and low-middle income countries.